Genetic (DNA) Vaccines - Yu. A. Popov; N. I. Mikshis (Проблемы особо опасных инфекций, 2010)
With the development of various branches of medicine and biology the classical ideas about means to prevent infectious diseases have changed. Nowadays in different countries of the world, investigations are carried out intensively in the sphere of genetic vaccines. Distinctive feature of DNA-vaccination is long lasted expression in eukaryotic cell cytoplasm of nucleic acids encoding synthesis of immunogenic proteins. Genetic vaccines induce both humoral and cellular responses accompanied by production of large pool of immunological memory cells. A number of questions regarding features of gene-engineered construction and transfer of DNA-vaccines into the cells of macroorganism, structure of DNA-vaccines and mechanisms of immune response generation are considered in the review. Attention is paid on the safety of gene vaccination and ways to improve its efficiency.